Forms of Liability of Minimarket Businesses for the Transfer of Money Back: Bentuk Pertanggungjawaban Pelaku Usaha Minimarket atas Pengalihan Uang Kembalian - Ilman, Mohamad Yazid; Mediawati, Noor Fatimah (Universitas Muhammadiyah Sidoarjo, 2021)
Donation, is one of the activities that has become a trend lately, many organizations and even individuals are competing in making donations. As is the case, what is done by minimarkets that carry out donation activities from the rest of the consumer's change. On this basis, a study entitled